Modeling of multi-junction photovoltaic cell using MATLAB/Simulink to improve the conversion efficiency - Das, N.; Wongsodihardjo, H.; Islam, Syed (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
© 2014 Elsevier Ltd. This paper focuses on modeling of multi-junction solar cell (MJSC) to improve the conversion efficiency using MATLAB/Simulink software. The multi-junction photovoltaic (PV) cell is investigated to obtain its maximum performance compare to the conventional silicon PV cell. MATLAB/Simulink modeled results show that tandem cell can provide almost 3-times maximum power compared to the conventional PV cells. Maximum power point tracker (MPPT) has also been performed to improve the conversion efficiency of the PV systems. The MPPT is able to assist the PV cells to attain more power efficiently and deliver electricity to the grid.